Reducing antimicrobial resistances by source separation of domestic wastewater - Londong, Jörg; Barth, Marcus; Söbke, Heinrich (Frontiers in Environmental Health, 2023)
Antimicrobial resistances (AMR) are ranked among the top ten threats to public health and societal development worldwide. Toilet wastewater contained in domestic wastewater is a significant source of AMR entering the aquatic environment. The current commonly implemented combined sewer systems at times cause overflows during rain events, resulting in the discharge of untreated wastewater into the aquatic environment, thus promoting AMR. In this short research article, we describe an approach to transform combined sewer systems into source separation-modified combined sewer systems that separately treat toilet wastewater. We employ simulations for demonstrating that source separation-modified combined sewer systems reduce the emission of AMR-causing substances by up to 11.5 logarithm levels. Thus, source separation-modified combined sewer systems are amongst the most effective means of combating AMR.